A New Pneumococcal Capsule Type, 10D, is the 100th Serotype and Has a Large cps Fragment from an Oral Streptococcus - Feroze Ganaie (American Society for Microbiology, 2020)
ABSTRACT Streptococcus pneumoniae (pneumococcus) is a major human pathogen producing structurally diverse capsular polysaccharides. Widespread use of highly successful pneumococcal conjugate vaccines (PCVs) targeting pneumococcal capsules has greatly reduced infections by the vaccine types but increased infections by nonvaccine serotypes. Herein, we report a new and the 100th capsule type, named serotype 10D, by determining its unique chemical structure and biosynthetic roles of all capsule synthesis locus (cps) genes. The name 10D reflects its serologic cross-reaction with serotype 10A and appearance of cross-opsonic antibodies in response to immunization with 10A polysaccharide in a 23-valent pneumococcal vaccine. Genetic analysis showed that 10D cps has three large regions syntenic to and highly homologous with cps loci from serotype 6C, serotype 39, and an oral streptococcus strain (S. mitis SK145). The 10D cps region syntenic to SK145 is about 6 kb and has a short gene fragment of wciNα at the 5′ end. The presence of this nonfunctional wciNα fragment provides compelling evidence for a recent interspecies genetic transfer from oral streptococcus to pneumococcus. Since oral streptococci have a large repertoire of cps loci, widespread PCV usage could facilitate the appearance of novel serotypes through interspecies recombination. IMPORTANCE The polysaccharide capsule is essential for the pathogenicity of pneumococcus, which is responsible for millions of deaths worldwide each year. Currently available pneumococcal vaccines are designed to elicit antibodies to the capsule polysaccharides of the pneumococcal isolates commonly causing diseases, and the antibodies provide protection only against the pneumococcus expressing the vaccine-targeted capsules. Since pneumococci can produce different capsule polysaccharides and therefore reduce vaccine effectiveness, it is important to track the appearance of novel pneumococcal capsule types and how these new capsules are created. Herein, we describe a new and the 100th pneumococcal capsule type with unique chemical and serological properties. The capsule type was named 10D for its serologic similarity to 10A. Genetic studies provide strong evidence that pneumococcus created 10D capsule polysaccharide by capturing a large genetic fragment from an oral streptococcus. Such interspecies genetic exchanges could greatly increase diversity of pneumococcal capsules and complicate serotype shifts.